Carriage and Resistance Pattern of Methicillin Resistant Staphylococcus aureus among Pregnant Women Attending an Ante- Natal Clinic in Uyo – Nigeria - Udobi, Chinweizu Ejikeme; Udochukwu, Nwaokonko Joseph; Chinaza, Onwubiko; Udobi, Ugochi Juliet (Nigerian Journal of Pharmaceutical and Applied Science Research, 2020)
The study was designed to investigate the carriage and resistance pattern of Methicillin resistant Staphylococcus aureus among pregnant women attending ante-natal clinic at the university of Uyo medical centre in Nigeria. Seventy (70) urine samples collected from pregnant women were screened for Staphylococcus aureus using standard microbiological techniques. The isolates were then subjected to antibiotic susceptibility testing using the disc diffusion method during which resistance to 30?g cefoxitin was used as a yardstick for Methicillin resistance. Results obtained showed that 50 (71%) of the urine samples were positive for Staphylococcus aureus and 21 (42%) of them were resistant to 30?g cefoxitin confirming them phenotypic MRSA isolates. Results obtained further showed that the MRSA isolates were resistant to norfloxacin (100%), ampicillin/cloxacin (81%), chloramphenicol (62%) but showed low resistance to levofloxacin (19%) and streptomycin (19%). Results obtained further confirmed that 76% of the MRSA isolates were multi- drug resistant and may have been contracted from the environment where they reside before coming to hospital. It is concluded that methicillin resistant Staphylococcus aureus (MRSA) carriage is still high among pregnant women in Uyo-Nigeria and the implications are highlighted.